VII—The Significance of Self‐Consciousness in Idealist Theories of Logic. Issue 2 (July 2014) - Pippin, Robert
Abstract : Among Kant's innovations in the understanding of logic ('general logic') were his claims that logic had no content of its own, but was the form of the thought of any possible content, and that the unit of meaning, the truth‐bearer, judgement, was essentially apperceptive. Judging was implicitly the consciousness of judging. This was for Kant a logical truth. This article traces the influence of the latter claim on Fichte, and, for most of the discussion, on Hegel. The aim is to understand the relations among self‐consciousness, reason and freedom in the idealist tradition.